2021
DOI: 10.1007/s00455-021-10271-x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cerebellum in Swallowing

Abstract: Swallowing is a complex activity requiring a sophisticated system of neurological control from neurones within the brainstem, cerebral cortices and cerebellum. The cerebellum is a critical part of the brain responsible for the modulation of movements. It receives input from motor cortical and sensory areas and fine tunes these inputs to produce coordinated motor outputs. With respect to swallowing, numerous functional imaging studies have demonstrated increased activity in the cerebellum during the task of swa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 78 publications
4
25
0
4
Order By: Relevance
“…In front of it are the pons, medulla, and fourth cerebral ventricle. The tentorium cerebelli and all cerebellar connections with other areas of the brain pass through the pons, which is separated from the overlaying cerebrum by a layer of leathery dura mater (1) .…”
Section: Introductionmentioning
confidence: 99%
“…In front of it are the pons, medulla, and fourth cerebral ventricle. The tentorium cerebelli and all cerebellar connections with other areas of the brain pass through the pons, which is separated from the overlaying cerebrum by a layer of leathery dura mater (1) .…”
Section: Introductionmentioning
confidence: 99%
“…Common clinical manifestations of ALS, such as pseudobulbar affect, dysarthria, dysphagia, eye movement abnormalities, behavioural dysfunction and deficits in social cognition, are often exclusively linked to corticobulbar tract degeneration, brainstem and cranial nerve pathology, orbitofrontal atrophy, etc, which overlooks the likely contribution of cerebellar pathology to these symptoms. [5][6][7] The pitfalls of linking imaging findings directly to clinical observations are well recognised, 8 but the real value of computational imaging in ALS lies in its ability to characterise disease burden patterns in vivo in an impartial, descriptive, observerindependent fashion. Varying patterns of cerebellar changes have been noted on whole-brain analyses, 9 but relatively few dedicated cerebellar studies have been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from its involvement in the movement required to locate food and bring it to the mouth, the cerebellum contributes to the two main motor components of consuming food: mastication (chewing) and swallowing [43]. Cerebellar injuries, stroke, and ataxia are associated with difficulties swallowing (dysphagia) and chewing [44,45,46,47,48], demonstrating the importance of an intact cerebellum in the physical ability to eat. This section will discuss the role of the cerebellum in both the voluntary (mastication and initiation of swallowing) and involuntary (passive swallowing) motor aspects of food ingestion.…”
Section: Cerebellar Contributions To Motor Control Of Eatingmentioning
confidence: 99%
“…Swallowing can be divided into three phases: (i) the oral preparatory phase, comprising of the formation of the bolus and voluntary guidance towards the larynx; (ii) the pharyngeal transfer phase, where a series of reflexes induce involuntary closure of the epiglottis and guidance of the bolus towards the oesophagus; and (iii) the oesophageal transport phase, when the bolus is transported towards the stomach by synchronised contraction and relaxation of the circular muscles [21]. Based on anatomical, physiological, imaging, and clinical evidence, the cerebellum has an established role in all phases of swallowing (for a more extensive review, see [48]). For example, fMRI studies in humans have shown cerebellar activation during swallowing, particularly within the left-hand side of the cerebellum (around lobule VI, vermal culmen and pyramis) [62,63,64].…”
Section: Cerebellum In Swallowingmentioning
confidence: 99%